(untitled) (Промышленный Транспорт Казахстан, 2025)
This article discusses the features and problems of developing of the transport sector in the Republic of Kazakhstan, which needs further reform. The entry of the Republic of Kazakhstan into the club of the most developed countries of the world implies the advanced development of the transport complex of the Republic, since it provides stable satisfaction of the transport needs of the national economy and population. The transport and logistics system of Kazakhstan, on the one hand, depends on existing external factors, on the other – is still in the process of formation. External factors shape the demand for services in the transport and logistics sector, but the existing problems do not fully contribute to the growth of this industry. In the context of growing international cooperation, the transport and logistics sector requires further modernization and expansion of infrastructure capacity in the near future. There is a need to review domestic policies regarding incentives for existing transport and logistics system facilities, such as rail and road connections and logistics centers. In addition, the lack of financing for small and medium-sized businesses does not ensure the growth of the transport industry